Agama dan Masalah Makna Dalam Teori Sosiologis Talcott Parsons - Marlian Arif Nasution (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
The social system always tends to move towards a balance that is dynamic, gradual (slowly or gradually) through adjustments and is not revolutionary. Several functional requirements or requirements that must be met in order for a social system to survive include the following functional imperatives: Adaptation, Goal Attainment, Integration, and Latency or commonly abbreviated as AGIL (Adaptation, Goal Attainment, Integration, Latency). That human action is seen as the smallest and basic social reality that is always driven by a (voluntaristic) will to achieve goals by heeding agreed values, ideas and norms. the relationship between religion and society, society and its community must have high moral ethics in order to maintain their solidarity. Belief in religion provides principles for society, while religious rituals are a way to generate commitment to these principles.